IMPLEMENTASI FRAMEWORK CODEIGNITER PADA PERANCANGAN APLIKASI PENGOLAHAN NILAI SISWA DI SMA ZION MAKASSAR - Edric; Hamdan Arfandy; Hendra Surasa (KHARISMA Tech, 2018)
This research aims to implementation a web-based programm in designing Students Value Processing Application at Zion High School Makassar .The system development process is performed using the PHP Programming Language. Furthermore, using the MVC (Model View Controller) concept will be implemented using the CodeIgniter Framework. The process of implementing the concept of MVC (Model View Controller) split between the database logic, view logic and then will be combined with database logic into one (1) data that called controller that used to arrange the work flow of the system. The evaluation show the result from MVC (Model View Controller) concept will be implemented with PHP programming, where the system can help input and processing values by online